1999
DOI: 10.1007/s004170050331
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological abnormalities in age-related macular degeneration

Abstract: In addition to data from psychophysical tests the results from electrophysiological examinations indicated a global reduction of retinal function in ARMD which seemed to be present not only in the macula but also elsewhere in the retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 24 publications
9
47
0
2
Order By: Relevance
“…This is in accordance with evidence that AMD related abnormalities extend beyond the parafovea, especially as the disease progresses. 20,30,[36][37][38][39][40] For example, Owsley et al 40 demonstrated a significant deficit NC indicates that rod intercept could not be calculated due to threshold dropping too rapidly to below 3.0 log units of stimulus attenuation (due to insufficient bleach intensity or bleach ineffectively delivered), UD indicates unreliable data (fixation errors exceeding 30%). * RIT was not reached within the maximum test duration, and a value of 30 minutes was ascribed.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with evidence that AMD related abnormalities extend beyond the parafovea, especially as the disease progresses. 20,30,[36][37][38][39][40] For example, Owsley et al 40 demonstrated a significant deficit NC indicates that rod intercept could not be calculated due to threshold dropping too rapidly to below 3.0 log units of stimulus attenuation (due to insufficient bleach intensity or bleach ineffectively delivered), UD indicates unreliable data (fixation errors exceeding 30%). * RIT was not reached within the maximum test duration, and a value of 30 minutes was ascribed.…”
Section: Discussionmentioning
confidence: 99%
“…1 Based on electrophysiological testing, it remains controversial whether rods are primarily affected or both rods and cones are similarly affected. [24][25][26][27][28][29][30][31][32][33] Microperimetry has detected photoreceptor abnormalities even before GA develops, and this strategy can also predict the area where existing GA will likely progress. [34][35][36][37][38][39][40] These histopathologic, electrophysiologic, and microperimetric findings in eyes with GA, along with the early visual function deficits and symptoms observed in patients even before GA develops, 41 suggest that photoreceptor dysfunction precedes the appearance and progression of GA in some eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Currently available approaches to objectively evaluate macular function include conventional electrophysiological tests and newer multifocal techniques. [1][2][3][4] Owing to the relatively low sensitivity and specificity of conventional electrophysiological tests in macular diseases, multifocal techniques, especially multifocal electroretinograms, have gained increasing popularity in the evaluation of macular diseases. Although a large number of studies have evaluated the use of multifocal electroretinograms in evaluating macular dysfunction, few studies have assessed the use of multifocal visual evoked potentials (mfVEP) in macular diseases.…”
Section: Introductionmentioning
confidence: 99%